2020
DOI: 10.1136/bmjdrc-2019-001155
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficacy and safety of insulin detemir versus neutral protamine hagedorn insulin in treatment of diabetes during pregnancy: a randomized, controlled study

Abstract: ObjectiveTo compare the efficacy and safety of insulin detemir (IDet) versus neutral protamine Hagedorn (NPH) insulin used in pregnant women with diabetes.Research design and methodsA randomized study was conducted in diabetic pregnant women (n=240) (including 132 with pregestational diabetes and 108 with gestational diabetes). All patients were randomly divided into two groups: IDet group (n=120) treated with IDet plus short acting insulin Novolin-R before three meals (RRR–IDet plan), and NPH group treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The prevalence of gout is increasing and can be exacerbated due to T2DM as well 43 . We are going to investigate the relationship between breakfast and dinner energy or macronutrient intake and the risk of T2DM in people with gout and other vulnerable groups including pregnant women 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of gout is increasing and can be exacerbated due to T2DM as well 43 . We are going to investigate the relationship between breakfast and dinner energy or macronutrient intake and the risk of T2DM in people with gout and other vulnerable groups including pregnant women 4 …”
Section: Discussionmentioning
confidence: 99%
“…An epidemiological survey confirmed that China had the largest number of T2DM patients and the prevalence of T2DM in China had reached 10.9% 3 . The prevalence of gestational diabetes and prepregnancy diabetes mellitus is increasing year by year, especially for gestational diabetes 4 . A scientific and appropriate diet, as an important modifiable behavior, plays a critical role in the prevention and management of T2DM 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Insulin determir demonstrates non-inferiority to NPH in achieving glycaemic control for patients with GDM and Type 2 Diabetes Mellitus and reaches this goal with fewer episodes of hypoglycaemia [106]. Insulin determir has also been found to reach glycaemic targets quicker than NPH thus necessitating fewer daily injections, an important patient acceptability metric [107]. Short acting insulin analogs formulated through amino acid substitution on the beta chain, include insulin lispro and aspart.…”
Section: Insulinmentioning
confidence: 99%
“…An Endocrine Society Clinical Practice Guideline recommends that diabetic women who receive insulin therapy and want to conceive should be treated with insulin lispro or insulin aspart instead of regular insulin, and those who successfully used long-acting insulin analogs before pregnancy can continue to use this treatment during pregnancy [144]. Studies have shown that the use of insulin detemir can improve fasting blood glucose levels and reduce the incidence of hypoglycemia without increasing the incidence of adverse pregnancy and drug reactions in pregnant women with diabetes [145][146][147][148][149]. A randomized controlled study reported no nocturnal hypoglycemia in the detemir group, and hypoglycemia occurred before lunch; however in the NPH group, hypoglycemia was irregular, and nocturnal hypoglycemia threatened the safety of the fetus [147].…”
Section: Insulin In Pregnant Patients With Dkdmentioning
confidence: 99%
“…Studies have shown that the use of insulin detemir can improve fasting blood glucose levels and reduce the incidence of hypoglycemia without increasing the incidence of adverse pregnancy and drug reactions in pregnant women with diabetes [145][146][147][148][149]. A randomized controlled study reported no nocturnal hypoglycemia in the detemir group, and hypoglycemia occurred before lunch; however in the NPH group, hypoglycemia was irregular, and nocturnal hypoglycemia threatened the safety of the fetus [147].…”
Section: Insulin In Pregnant Patients With Dkdmentioning
confidence: 99%